Can a fibrotic liver afford epithelial-mesenchymal transition? - Munker, Stefan; Liebe, Roman; Weng, Honglei (World journal of gastroenterology, 2017)
The question whether epithelial-mesenchymal transition (EMT) occurs during liver fibrogenesis is a controversial issue. In vitro studies confirm that hepatocytes or cholangiocytes undergo EMT upon transforming growth factor β (TGF-β) stimulation, whereas in vivo experiments based on genetic fate mapping of specific cell populations suggest that EMT does not occur in fibrotic animal models. In this review we present current data supporting or opposing EMT in chronic liver disease and discuss conditions for the occurrence of EMT in patients. Based on the available data and our clinical observations we hypothesize that EMT-like alterations in liver cirrhosis are a side effect of high levels of TGF-β and other pro-fibrotic mediators rather than a biological process converting functional parenchyma, i.e., hepatocytes, into myofibroblasts at a time when essential liver functions are deteriorating.
Gesehen am 05.06.2018